The Influence of Al-Qur’an and Hadith Learning on Qur’an Reading Ability in Grade 4 at Madrasah Ibtidaiyah Negeri 28 Hulu Sungai Utara - Annisa Annisa; Ria Susanti; Syahrani Syahrani (Al Husna: Jurnal Ilmiah Pendidikan Agama Islam, 2024)
This research is motivated by the importance of the ability to read the Qur’an in Islam, where recitation must follow the proper tajwid rules in order to serve as a purpose and guidance for life in this world and the hereafter. Learning about recitation rules is included in the Al-Qur’an Hadith subject, especially for Grade 4 students of MIN 28 Hulu Sungai Utara. This study aims to determine the influence of Al-Qur’an Hadith learning on the Qur’an reading ability of Grade 4 students at MIN 28 Hulu Sungai Utara. The research was conducted at MIN 28 Hulu Sungai Utara, Amuntai–South Kalimantan. The population and sample consisted of all 30 Grade 4 students. Data collection techniques included observation, questionnaires, and documentation. The data were processed using checking, editing, coding, scoring, tabulating, and data interpretation techniques, followed by data analysis. Based on the results obtained from the study, there is a significant influence between Al-Qur’an Hadith learning and the Qur’an reading ability of Grade 4 students at MIN 28 Hulu Sungai Utara. Thus, the hypothesis is accepted because the calculated r value is greater than the r table at both the 5% and 1% significance levels.